Applications of graphene in microbial fuel cells: The gap between promise and reality. (May 2017) - ElMekawy, Ahmed; Hegab, Hanaa M.; Losic, Dusan; Saint, Christopher P.; Pant, Deepak
Abstract: Since the initial emergence of two-dimensional graphene (Gr) nano-material, there has been a great interest in its potential applications due to its excellent conductivity, enormous surface area and good mechanical strength. Microbial fuel cells (MFCs) are one of these important promising applications. The limited productivity of MFCs compared to other fuel cell technologies along with the high cost of their components are the two major obstacles to commercialization. Gr is proposed to help overcome such challenges by integrating with biocatalysts for the construction of Gr based MFCs, either as an anode to increase the electron transfer efficiency, or as a cathode to effectively catalyze the oxygen reduction reaction (ORR). This integration is relevant only if the favorable environment for bacterial biofilm adherence to Gr modified surfaces is available. Unfortunately, there is insufficient understanding of the interaction mechanism of bacterial cells with such modified surfaces. Despite this challenge, along with the complexity of the Gr modified electrode fabrication, Gr-based electrodes remain a promising option for developing MFCs to achieve sustainable wastewater treatment and bioelectricity generation. As a reflection on these facts, the aim of this review is to provide critical overview and to evaluate the recent advances for the applications of Gr in MFCs, focusing on electrode fabrication and power generation. Within that context, the concerns about microbial compatibility of Gr will be addressed.